Radiation of sound waves by semi-perforated duct - Tiryakioglu, Burhan; Ozturk, Hulya (Taylor & Francis Ltd, 2022)
In this paper, the Wiener-Hopf method is studied to solve the radiation of acoustic waves from a perforated part through an infinite channel. At first the boundary value problem involving a Helmholtz equation with mixed-boundary conditions is formulated into a Wiener Hopf equation by applying the Fourier transform. After that the Wiener-Hopf kernel is split into two functions that are analytic in specified regions of the complex-plane and equation is solved analytically. Finally, numerical results showing the effect of the problem's parameters (channel radius, frequency, etc.) on the radiation phenomenon are graphically displayed.
Keywords: Fourier transform; Wiener-Flopf method; Boundary value problem; Radiation; Acoustics